Ultrasound-guided peripheral nerve interventions for common pain disorders - PKrishna Prasad, B; Joy, Binu; Raghavendra, Vijayakumar A; Toms, Ajith; George, Danny; Ray, Brijesh (Indian Journal of Radiology and Imaging, 2018)
There are a number of common pain disorders that can be managed effectively by injections around or ablation of peripheral nerves. Ultrasound is a universally available imaging tool, is safe, cost-effective, and is excellent in imaging many peripheral nerves and guiding needles to the site of the nerves. This article aims to present an overview of indications and techniques of such procedures that can be effectively performed by a radiologist.
Keywords: Ganglion block; nerve block; perineural injection